How Foreign Direct Investment Promotes Development: The Case of the People's Republic of China's Inward and Outward FDI - Zhongmin Li (Asian Development Bank (ADB), 2013)
In the last 33 years after the People's Republic of China's (PRC) openness and reform, huge amounts of foreign direct investment (FDI) flowed into the PRC. The capital inflow and technology spillover in turn enabled outward FDI from the PRC. This paper gives a brief introduction to the PRC's inward and outward FDI, including their determinants, motives, main characteristics, and impact on the PRC and host countries. Inward FDI contributes to the PRC's economic growth and industry development, increases tax revenue, and improves labor quality. The contribution of inward FDI to gross domestic product averages around 3%–6%. At the same time, outward FDI improves the PRC's dynamic efficiency, and helps the host countries with capital inflow and infrastructure improvement. Based on the PRC's experience, four policy issues are proposed: dynamic mechanism inside FDI, investment liberalization, international coordination, and trade-related policy.
hdl:11540/2092
Keywords: E22; F21; O53; 330; FDI; PRC; South–South investment; Auslandsinvestition; Wirkungsanalyse; China